Nursing a Patient with Nonepileptic Seizures — Case Report - Piotr Wojda (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Differentiation of epileptic seizures from psychogenic nonepileptic seizures (PNES) is problematic and leads to wrong diagnosis. It is estimated that among patients diagnosed with epilepsy, as many as 20–40% suffered from pseudo-epileptic seizures. Misdiagnosis is associated with a delay in the implementation of appropriate treatment, complications following unnecessary treatment, worse functioning of the patient, high costs of care and unemployment. Aim. The aim of the study was to familiarise neuroscience nurses with the causes, symptoms, treatment and nursing care for a patient with PNES on the basis of the described case. Case Report. Case study of a female patient with psychogenic non-epileptic seizures repeatedly treated in a psychiatric ward. Based on an interview with the patient, analysis of the medical documentation, direct and indirect observation of the patient, problems with nursing were identified and a care plan was established. Results. The depicted patient was admitted to a psychiatric ward due to suicidal intentions, decreased mood and epileptic attacks of unknown aetiology. The patient was struggling with numerous psychosocial problems, which required high professional and ethical competences. The patient has been diagnosed with the following care problems: reluctance to undergo video EEG examination, abdominal pain, isolation of the patient in the ward, risk of suicide, risk of injury. Conclusions. The nursing interventions undertaken with respect to the patient turned out to be effective. Improvement in psychosocial functioning was achieved and the patient did not attempt suicide during the crisis. Thanks to the interdisciplinary cooperation, it was possible to confirm the non-epileptic nature of the seizures, and the patient was discharged with therapeutic recommendations (pharmacotherapy, psychotherapy, visits to a mental health clinic). (JNNN 2021;10(1):35–41)